Oscillator design and computer simulation - Rhea, Randall W. (Raleigh, NC SciTech Publishing, Inc., 1995)
This second edition of the number one guide to oscillator design presents a comprehensive, unified approach to oscillator design that can be used with a wide range of active devices and resonator types. Resonator types covered include: L-C, crystal, SAW, dielectric resonator, coaxial line, stripline and microstrip. This text covers modern CAD synthesis and analysis techniques and is valuable to experienced engineers as well as to those new to oscillator design. The books topics include: Analysis fundamentals, oscillator fundamentals, limiting and starting, biasing, noise, computer simulation and examples and case studies.
Electronic reproduction.
Keywords: Oscillators, Electric -- Computer simulation; Radio frequency oscillators -- Design and construction; Oscillators, Microwave -- Design and construction; Electronic books